Forensic science, genetics and wildlife biology: getting the right mix for a wildlife DNA forensics lab - Ogden, Rob (Forensic science, medicine, and pathology, 2010)
Wildlife DNA forensics is receiving increasing coverage in the popular press and has begun to appear in the scientific literature in relation to several different fields. Recognized as an applied subject, it rests on top of very diverse scientific pillars ranging from biochemistry through to evolutionary genetics, all embedded within the context of modern forensic science. This breadth of scope, combined with typically limited resources, has often left wildlife DNA forensics hanging precariously between human DNA forensics and academics keen to seek novel applications for biological research. How best to bridge this gap is a matter for regular debate among the relatively few full-time practitioners in the field. The decisions involved in establishing forensic genetic services to investigate wildlife crime can be complex, particularly where crimes involve a wide range of species and evidential questions. This paper examines some of the issues relevant to setting up a wildlife DNA forensics laboratory based on experiences of working in this area over the past 7 years. It includes a discussion of various models for operating individual laboratories as well as options for organizing forensic testing at higher national and international levels.